High-strength impact-resistant composite heat-resistant plate and preparation method thereof
Through the crosslinking technology of modified nano calcium carbonate and halogen-free flame retardant and polypropylene resin, the problems of improving strength, impact resistance and heat resistance of composite plates are solved, and excellent flame retardant and smoke resistance and antibacterial properties are achieved. .
Patent Information
- Application Number
- CN202411818892.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After the addition of inorganic materials, the strength, impact resistance and heat resistance of existing composite panels cannot be effectively improved, and the flame retardant and smoke inhibiting performance and antibacterial properties are insufficient.
Modified nano calcium carbonate and halogen-free flame retardant are used to cross-link with polypropylene resin to form a stable hybrid network structure, improving the mechanical properties and flame retardant properties of the composite panel, while increasing antibacterial properties.
It significantly improves the strength, impact resistance and heat resistance of the composite panel, and improves its flame retardant, smoke resistance and antibacterial properties, making it excellent stability and durability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular, relates to a high-strength impact-resistant composite heat-resistant plate and a preparation method thereof. Background Art
[0002] Composite board is a new type of material that is mixed with thermoplastic polymer materials, processing aids and wood cellulose or plant cellulose and then heated and formed by mold equipment. It has excellent dimensional stability, corrosion resistance and water resistance, and is widely used.
[0003] In the prior art, inorganic materials are generally added to the composite board for modification to increase the strength, impact resistance and heat resistance of the composite board. However, the surface of inorganic materials is generally hydrophilic and oleophobic, and has poor affinity with polymer resins and is easy to form aggregates, resulting in internal defects in the polymer and poor mechanical properties, which cannot improve the strength, impact resistance and heat resistance of the composite board. In addition, it is also very important to improve the flame retardant, smoke suppression and antibacterial properties of the composite board. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high-strength impact-resistant composite heat-resistant plate and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-strength impact-resistant composite heat-resistant board comprises the following raw materials in parts by weight: 100-110 parts of polypropylene resin, 20-30 parts of wood flour, 20-30 parts of modified nano calcium carbonate, 5-10 parts of flame retardant, 4-9 parts of compatibilizer, 2-5 parts of aramid fiber, 2-4 parts of sepiolite fiber, 2-4 parts of glass fiber, 1-2 parts of ultraviolet absorber, 1-2 parts of antioxidant, and 0.1-0.2 parts of cross-linking agent.
[0006] Furthermore, the modified nano calcium carbonate is prepared by the following steps: (1) A dry three-necked flask was blown with nitrogen to expel air and moisture from it, and then 4-chloro-1-butene, pyridine and chloroform were added. After stirring and dissolving, the temperature was raised to 60°C, and KH540 (3-aminopropyltrimethoxysilane) was slowly added. After the addition was completed, the temperature was kept at 60°C for 3 h. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 1. The dosage ratio of KH540, 4-chloro-1-butene, pyridine and chloroform was 34.9 mL:41.9 mL:35 mL:180 mL. Pyridine is used as an acid binding agent to control the molar ratio of KH540 to 4-chloro-1-butene to be 1:2.05-2.1. 2 The -Cl of 4-chloro-1-butene undergoes a di-substitution reaction under heating, and the reaction process is as follows:
[0007] (2) Under nitrogen protection, intermediate 1, pyridine and chloroform were added to a dry three-necked flask, stirred and dissolved, and then heated to 65°C, and then tetradecane bromide was slowly added. After the addition was completed, the temperature was kept at 65°C for 4 hours. After the reaction was completed, it was cooled to room temperature and then distilled under reduced pressure to obtain intermediate 2; the amount ratio of intermediate 1, tetradecane bromide, pyridine and chloroform was 43g:47.8mL:13.5mL:200mL; Pyridine is used as an acid binding agent, and the molar ratio of intermediate 1 to tetradecane bromide is controlled to be 1:1.05-1.1. The -NH- of intermediate 1 and the -Cl of tetradecane bromide undergo a substitution reaction under heating. The reaction process is shown below:
[0008] (3) Mix nano-calcium carbonate and deionized water in a three-necked flask, then slowly add acetic acid to adjust the pH to 4, then slowly add the mixed solution of intermediate 2 and chloroform while stirring, heat to 65°C after the addition is completed, keep warm for 1 hour, cool to room temperature after the reaction is completed, and then centrifuge. After centrifugation, take the precipitate and ultrasonically disperse it in anhydrous ethanol for 0.5 hour, and finally dry it at 80°C for 12 hours to obtain modified nano-calcium carbonate; the dosage ratio of nano-calcium carbonate, intermediate 2, chloroform and deionized water is 40g:4g:20mL:250mL.
[0009] The silaneoxy groups on the surface of the intermediate 2 are hydrolyzed under heating and acidic conditions, and then chemically bonded with the hydroxyl groups on the surface of the nano-calcium carbonate to obtain modified nano-calcium carbonate.
[0010] The interface compatibility between modified nano-calcium carbonate and polypropylene resin is high, and the surface of modified nano-calcium carbonate contains oil-soluble long carbon chain in addition, according to similar compatibility principle, the compatibility between modified nano-calcium carbonate and all other organic raw materials also increases greatly, thereby the tensile strength, flexural strength and notched impact strength of the composite board containing modified nano-calcium carbonate are greatly improved. In addition, quaternary ammonium salt is contained in the modified nano-calcium carbonate, and quaternary ammonium salt can improve the antibacterial property and antistatic property of the composite board. The terminal carbon-carbon double bond on the surface of modified nano-calcium carbonate can produce chemical reaction with the carbon-carbon double bond in the fire retardant under the effect of cross-linking agent, and this chemical reaction can promote the stability and dispersion of modified nano-calcium carbonate in the composite board, and can also promote the stability and dispersion of fire retardant, thereby modified nano-calcium carbonate of the present invention can give full play to the effect, effectively promote mechanical properties such as tensile strength, flexural strength and notched impact strength and antibacterial property, antistatic property of the composite board.
[0011] Furthermore, the flame retardant is prepared by the following steps: S1. Add 3-butene-1-ol and tetrahydrofuran to a dry three-necked flask, stir evenly, add phosphorus oxychloride and pyridine, put the flask in an ice-water bath at 0°C to react for 1 hour, centrifuge the product after the reaction, and then dry it at 80°C for 12 hours to obtain intermediate 3; the amount ratio of phosphorus oxychloride, 3-butene-1-ol, pyridine and tetrahydrofuran is 18.6mL:18mL:17.8mL:160mL; In an ice water bath, pyridine is used as an acid binding agent, and the dosage ratio of phosphorus oxychloride and 3-butene-1-ol is controlled to be 1:1-1.05, then phosphorus oxychloride and 3-butene-1-ol undergo esterification reaction, and the reaction process is as follows:
[0012] S2. Add 1-tetradecanol and dimethyl sulfoxide to a dry three-necked flask, stir evenly, then add intermediate 3 and pyridine, place the flask in an ice-water bath (0°C) to react for 1.5 hours, centrifuge the product after the reaction, and then dry it at 80°C for 12 hours to obtain intermediate 4; the amount ratio of intermediate 3, 1-tetradecanol, pyridine and dimethyl sulfoxide is 28.3g:33.7g:13.3mL:220mL; In an ice-water bath, pyridine is used as an acid-binding agent, and the dosage ratio of intermediate 3 and 1-tetradecanol is controlled to be 1:1-1.05, then intermediate 3 and 1-tetradecanol undergo esterification reaction, and the reaction process is as follows:
[0013] S3. Blow nitrogen through a dry three-necked flask to expel air and moisture from the flask, then add intermediate 4, triethylamine and dimethyl sulfoxide, stir to dissolve, then add 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and stir to react at room temperature for 2 hours. After the reaction is completed, perform reduced pressure distillation to obtain a flame retardant; the amount ratio of intermediate 4, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, triethylamine and dimethyl sulfoxide is 34.3 g:12.4 mL:13.5 mL:200 mL.
[0014] The molar ratio of intermediate 4 and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is controlled to be 2.05-2.1:1, and then intermediate 4 and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane undergo a disubstitution reaction at room temperature, and triethylamine is used as an acid binding agent. The reaction process is as follows:
[0015] At high temperatures, the phosphorus element in the flame retardant provides an acid source, reacts with the polypropylene resin, and promotes the formation of carbonized products; the nitrogen element provides a gas source, causing the system to expand and foam, promoting the formation of a carbonized layer, and forming porous foamed carbon; the silicon element generates an inorganic heat-insulating and insulating protective layer containing -Si-O bonds and -Si-C- bonds during combustion, which not only prevents the decomposition products generated by combustion from escaping, but also inhibits the thermal decomposition of polymer materials, achieving the purpose of high flame retardancy, low smoke emission, and low harmfulness. Therefore, the flame retardant of the present invention exerts an efficient and safe flame retardant effect through the synergistic effect of the halogen-free flame retardant elements nitrogen, phosphorus, and silicon, so that the composite board has excellent flame retardancy and smoke suppression.
[0016] The long carbon chain in the flame retardant that can be freely extended and rotated can improve the mechanical properties of the composite board, such as toughness and impact strength. At the same time, the lipophilic long carbon chain also increases the compatibility between the flame retardant and the other raw materials, thereby improving the dispersion of the flame retardant. The carbon-carbon double bonds in the flame retardant can react chemically with the carbon-carbon double bonds at the end of the polypropylene that have not reacted completely and the carbon-carbon double bonds on the surface of the modified nano-calcium carbonate under the action of the cross-linking agent, so that the flame retardant can be highly dispersed and firmly present in the composite board. At the same time, the flame retardant, polypropylene resin and modified nano-calcium carbonate are cross-linked to form a stable hybrid network structure. This cross-linking structure not only allows the flame retardant and modified nano-calcium carbonate to be stably present in the composite board, but is not easy to migrate or fall out, thereby maximizing their role, giving the composite board excellent and stable mechanical properties, antibacterial properties and flame retardant properties, etc., but also makes the composite board more heat-resistant and more stable.
[0017] Sepiolite fiber and aramid fiber have good heat resistance and high strength, so they can work synergistically to improve the heat resistance, mechanical properties and processing properties of the composite board, while reducing production costs.
[0018] Furthermore, the compatibilizer is one or more of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, and ethylene-acrylate-maleic anhydride copolymer.
[0019] Furthermore, the ultraviolet absorber is one or more of ultraviolet absorber UV-P, ultraviolet absorber UV-531, ultraviolet absorber UVP-327, and light stabilizer 744.
[0020] Furthermore, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 1035, antioxidant 168, and antioxidant DLTP.
[0021] Furthermore, the cross-linking agent is one or both of benzoyl peroxide and triallyl isocyanurate.
[0022] A method for preparing a high-strength impact-resistant composite heat-resistant plate comprises the following steps: Weigh each raw material by weight and add it to a high-speed mixer for mixing. After mixing evenly, put it into an internal mixer for kneading. After the kneading is completed, put it into a twin-screw extruder for extrusion granulation. Then, the dried pellets are placed in a mold for compression molding, and finally cooled and cut to obtain a high-strength impact-resistant composite heat-resistant board.
[0023] The invention has the beneficial effects that the modified nano-calcium carbonate containing quaternary ammonium salt, the flame retardant containing halogen-free flame retardant elements and the polypropylene resin are cross-linked to form a stable hybrid network structure, and the cross-linked structure enables the flame retardant and the modified nano-calcium carbonate to be stably present in the composite board and not easy to migrate or escape, so that they can play their role to the maximum extent. In addition, due to the synergistic effect of other raw materials, the composite board of the invention has high strength, strong impact resistance, good heat resistance, and high-efficiency and lasting flame retardant effect and antibacterial property. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1, preparation of modified nano calcium carbonate, the specific steps are as follows: (1) Nitrogen was blown into a 500 mL dry three-necked flask to expel air and moisture from the flask, followed by the addition of 41.9 mL of 4-chloro-1-butene, 35 mL of pyridine and 180 mL of chloroform. After stirring and dissolving, the temperature was raised to 60°C, and 34.9 mL of KH540 was slowly added. After the addition was completed, the temperature was kept at 60°C for 3 h. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 1. (2) Under nitrogen protection, 43 g of intermediate 1, 13.5 mL of pyridine and 200 mL of chloroform were added to a 500 mL dry three-necked flask, stirred to dissolve, and then heated to 65°C. Then 47.8 mL of tetradecane bromide was slowly added. After the addition was completed, the temperature was kept at 65°C for 4 h. After the reaction was completed, it was cooled to room temperature and then distilled under reduced pressure to obtain intermediate 2; (3) 40 g of nano-calcium carbonate and 250 mL of deionized water were mixed evenly in a 500 mL three-necked flask, and acetic acid was slowly added to adjust the pH to 4. Subsequently, a mixed solution of 4 g of intermediate 2 and 20 mL of chloroform was slowly added while stirring. After the addition was completed, the temperature was raised to 65 °C and the reaction was kept warm for 1 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged. After centrifugation, the precipitate was ultrasonically dispersed in anhydrous ethanol for 0.5 h, and finally dried at 80 °C for 12 h to obtain modified nano-calcium carbonate.
[0026] Example 2, preparation of modified nano calcium carbonate, the specific steps are as follows: The remaining steps remain unchanged, only step (1) and step (2) of Example 1 are removed, and the intermediate 2 in step (3) is replaced by KH540 (3-aminopropyltrimethoxysilane) to prepare modified nano-calcium carbonate.
[0027] Example 3, preparation of modified nano calcium carbonate, the specific steps are as follows: The remaining steps remain unchanged, only step (1) and step (2) of Example 1 are removed, and the intermediate 2 in step (3) is replaced by vinyltrimethoxysilane to prepare modified nano-calcium carbonate.
[0028] Example 4, preparing a flame retardant, the specific steps are as follows: S1. Add 18 mL of 3-butene-1-ol and 160 mL of tetrahydrofuran into a 500 mL dry three-necked flask, stir evenly, add 18.6 mL of phosphorus oxychloride and 17.8 mL of pyridine, place the flask in an ice water bath at 0°C for 1 h, and after the reaction is completed, centrifuge the product for separation by centrifugal sedimentation, and then dry at 80°C for 12 h to obtain intermediate 3; S2, add 33.7g of 1-tetradecanol and 220mL of dimethyl sulfoxide into a 500mL dry three-necked flask, stir evenly, add 28.3g of intermediate 3 and 13.3mL of pyridine, put the flask into an ice water bath (0°C) to react for 1.5h, after the reaction is completed, centrifuge the product to separate by centrifugal sedimentation, and then dry at 80°C for 12h to obtain intermediate 4; S3. Blow nitrogen into a dry 500mL three-necked flask to expel air and moisture from the flask, add 34.3g of intermediate 4, 13.5mL of triethylamine and 200mL of dimethyl sulfoxide, stir to dissolve, then add 12.4mL of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, stir to react at room temperature for 2h, and distill under reduced pressure after the reaction is completed to obtain a flame retardant.
[0029] Example 5, preparing a high-strength impact-resistant composite heat-resistant plate, the specific steps are as follows: 100 parts of polypropylene resin, 20 parts of wood flour, 20 parts of modified nano calcium carbonate prepared in Example 1, 5 parts of flame retardant prepared in Example 4, 4 parts of maleic anhydride grafted polyethylene, 2 parts of aramid fiber, 2 parts of sepiolite fiber, 2 parts of glass fiber, 0.8 parts of ultraviolet absorber UV-P, 0.2 parts of light stabilizer 744, 1 part of antioxidant 1010, and 0.1 part of triallyl isocyanurate are weighed by weight and added into a high-speed mixer for mixing. After mixing evenly, the mixture is put into an internal mixer for mixing. After mixing, the mixture is put into a twin-screw extruder for extrusion granulation. Then, the dried pellets are placed in a mold for compression molding, and finally cooled and cut to obtain a high-strength impact-resistant composite heat-resistant board.
[0030] Example 6, preparing a high-strength impact-resistant composite heat-resistant plate, the specific steps are as follows: 105 parts of polypropylene resin, 26 parts of wood flour, 27 parts of modified nano calcium carbonate prepared in Example 1, 8 parts of flame retardant prepared in Example 4, 5 parts of ethylene-acrylate-maleic anhydride copolymer, 3 parts of aramid fiber, 3 parts of sepiolite fiber, 3 parts of glass fiber, 0.6 parts of ultraviolet absorber UV-531, 0.6 parts of antioxidant 1076, 0.2 parts of antioxidant 168, 0.2 parts of antioxidant DLTP and 0.15 parts of benzoyl peroxide were weighed by weight and added into a high-speed mixer for mixing. After mixing evenly, the mixture was put into an internal mixer for mixing. After mixing, the mixture was put into a twin-screw extruder for extrusion granulation. Then, the dried pellets were placed in a mold for compression molding, and finally cooled and cut to obtain a high-strength impact-resistant composite heat-resistant board.
[0031] Example 7, preparing a high-strength impact-resistant composite heat-resistant plate, the specific steps are as follows: 110 parts of polypropylene resin, 30 parts of wood flour, 30 parts of modified nano-calcium carbonate prepared in Example 1, 10 parts of flame retardant prepared in Example 4, 6 parts of maleic anhydride grafted polypropylene, 3 parts of maleic anhydride grafted polyethylene, 5 parts of aramid fiber, 4 parts of sepiolite fiber, 4 parts of glass fiber, 1.5 parts of ultraviolet absorber UVP-327, 0.5 parts of light stabilizer 744, 1 part of antioxidant 1098, 0.5 parts of antioxidant 1035, 0.25 parts of antioxidant 168, 0.25 parts of antioxidant DLTP, 0.1 parts of benzoyl peroxide and 0.1 parts of triallyl isocyanurate were weighed by weight and added into a high-speed mixer for mixing, mixed evenly and then put into an internal mixer for mixing, put into a twin-screw extruder for extrusion granulation after mixing, then the dried pellets were placed in a mold for compression molding, and finally cooled and cut to obtain a high-strength impact-resistant composite heat-resistant board.
[0032] Comparative Example 1: preparing a composite board, the specific steps are as follows: The remaining steps remain unchanged, only the modified nano-calcium carbonate in Example 5 is replaced by the modified nano-calcium carbonate prepared in Example 2, thereby preparing a composite board.
[0033] Comparative Example 2: preparing a composite board, the specific steps are as follows: The remaining steps remain unchanged, only the modified nano-calcium carbonate in Example 5 is replaced by the modified nano-calcium carbonate prepared in Example 3, thereby preparing a composite board.
[0034] Comparative Example 3: preparing a composite board, the specific steps are as follows: The remaining steps remain unchanged, except that the flame retardant in Example 5 is replaced by 3 parts of ammonium polyphosphate and 2 parts of aluminum hypophosphite, thereby preparing a composite board.
[0035] Performance Testing (1) The composite boards prepared in Examples 5-7 and Comparative Examples 1-3 were tested for antibacterial properties (Escherichia coli ATYCC25922, Staphylococcus aureus ATCC6538) according to GB / T31402-2015. The specific test results are shown in Table 1 below: Table 1 ; “-” means no antibacterial property.
[0036] From the test results in Table 1 above, it can be seen that the composite boards prepared in Examples 5-7 of the present invention have more excellent and stable antibacterial properties. From the comparison of the test results of Examples 5-7 and Comparative Example 3, it can be seen that there is an interaction between the flame retardant of the present invention and the modified nano-calcium carbonate, thereby ensuring the antibacterial stability of the composite board.
[0037] (2) The composite plates prepared in Examples 5-7 and Comparative Examples 1-3 were tested for limiting oxygen index according to GB / T 2406.2-2009; the impact strength was tested according to GB / T 29500-2013; the dimensional change rate after heating was tested at a temperature of 70°C and a test time of 48h. The test results of all items are shown in Table 2 below: Table 2 ; It can be seen from the test results in Table 2 above that the composite panels prepared in Examples 5-7 of the present invention have more excellent flame retardancy, impact strength and heat resistance.
[0038] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0039] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high-strength impact-resistant composite heat-resistant board, characterized in that: The invention comprises the following raw materials in parts by weight: 100-110 parts of polypropylene resin, 20-30 parts of wood flour, 20-30 parts of modified nano calcium carbonate, 5-10 parts of flame retardant, 4-9 parts of compatibilizer, 2-5 parts of aramid fiber, 2-4 parts of sepiolite fiber, 2-4 parts of glass fiber, 1-2 parts of ultraviolet absorber, 1-2 parts of antioxidant and 0.1-0.2 parts of cross-linking agent; Wherein, the modified nano calcium carbonate is prepared by the following steps: (1) After nitrogen was purged into the flask, 4-chloro-1-butene, pyridine and chloroform were added, the temperature was raised to 60°C, KH540 was added, the reaction was continued for 3 h, the reaction was cooled, and the intermediate 1 was obtained by distillation under reduced pressure; (2) Under nitrogen protection, intermediate 1, pyridine and chloroform were added to a flask, the temperature was raised to 65°C, tetradecane bromide was added, the reaction was continued for 4 hours, and the intermediate 2 was obtained by distillation under reduced pressure; (3) Mix nano calcium carbonate and deionized water in a flask, adjust the pH to 4, add intermediate 2 and chloroform, react at 65°C for 1 h, cool, centrifuge, take the precipitate, disperse it in anhydrous ethanol, and dry it to obtain modified nano calcium carbonate; The flame retardant is prepared by the following steps: S1. Add 3-butene-1-ol and tetrahydrofuran into a flask, stir, add phosphorus oxychloride and pyridine, react at 0°C for 1 h, centrifuge, and dry to obtain intermediate 3; S2, add 1-tetradecanol and dimethyl sulfoxide into a flask, stir, add intermediate 3 and pyridine, react at 0°C for 1.5h, centrifuge, and dry to obtain intermediate 4; S3. After nitrogen is blown into the flask, intermediate 4, triethylamine and dimethyl sulfoxide are added, and after stirring, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added. The reaction is carried out at room temperature for 2 hours, and the flame retardant is obtained by distillation under reduced pressure.
2. A high-strength impact-resistant composite heat-resistant plate according to claim 1, characterized in that: The amount ratio of KH540, 4-chloro-1-butene, pyridine and chloroform in step (1) is 34.9 mL: 41.9 mL: 35 mL: 180 mL; the amount ratio of intermediate 1, tetradecane bromide, pyridine and chloroform in step (2) is 43 g: 47.8 mL: 13.5 mL: 200 mL; the amount ratio of nano-calcium carbonate, intermediate 2, chloroform and deionized water in step (3) is 40 g: 4 g: 20 mL: 250 mL.
3. The high-strength impact-resistant composite heat-resistant plate according to claim 1, characterized in that: The amount ratio of phosphorus oxychloride, 3-butene-1-ol, pyridine and tetrahydrofuran in step S1 is 18.6 mL: 18 mL: 17.8 mL: 160 mL; the amount ratio of intermediate 3, 1-tetradecanol, pyridine and dimethyl sulfoxide in step S2 is 28.3 g: 33.7 g: 13.3 mL: 220 mL; the amount ratio of intermediate 4, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, triethylamine and dimethyl sulfoxide in step S3 is 34.3 g: 12.4 mL: 13.5 mL: 200 mL.
4. The high-strength impact-resistant composite heat-resistant plate according to claim 1, characterized in that: The compatibilizer is one or more of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, and ethylene-acrylate-maleic anhydride copolymer.
5. The high-strength impact-resistant composite heat-resistant plate according to claim 1, characterized in that: The ultraviolet absorber is one or more of the ultraviolet absorber UV-P, ultraviolet absorber UV-531, ultraviolet absorber UVP-327, and light stabilizer 744.
6. The high-strength impact-resistant composite heat-resistant plate according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 1035, antioxidant 168, and antioxidant DLTP.
7. The high-strength impact-resistant composite heat-resistant plate according to claim 1, characterized in that: The cross-linking agent is one or both of benzoyl peroxide and triallyl isocyanurate.
8. The method for preparing a high-strength impact-resistant composite heat-resistant plate according to claim 1, characterized in that: The following steps are involved: Weigh each raw material by weight and add it to a high-speed mixer for mixing. After mixing, put it into an internal mixer for kneading. After the kneading is completed, put it into a twin-screw extruder for extrusion granulation. The dried pellets are placed in a mold for compression molding, cooled and cut to obtain a high-strength impact-resistant composite heat-resistant board.
Citation Information
Patent Citations
Preparation method of bending-resistant jumper cable material for rail car
CN118931026A
Carboxamide or amine compound and preparation method and application thereof
WO2017128860A1
Flame-retardant antimicrobial agent, preparation method therefor and use thereof, and flame-retardant antimicrobial thermoplastic resin composition
WO2021083272A1
Cited By
Impact-resistant acrylic plate and preparation method thereof
CN120399379A